2013
DOI: 10.1080/09654313.2012.722932
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Inter-Municipal Collaboration: Evidence from Metropolitan Planning in Portugal

Abstract: Inter-organisational collaboration as a means for policy coordination has come to be seen as a solution to difficult and complex urban challenges. In Portugal, where metropolitan governance structures are highly fragmented, critics highlight the need for better coordination between municipalities-a situation typical in many countries. We seek to understand the forces behind the emergence of inter-municipal collaboration around land use and mobility issues, using a case study method. Based on nine cases from Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…The central government could also test the effectiveness of, and build the capacity of, the AMTs by endowing them with some grant-making capabilities. For example, Rayle and Zegras (2012), in an analysis of inter-municipal collaboration in Portugal, find evidence supporting the role of financial incentives in inducing such collaboration. Perhaps the AMTs could be enabled to deploy modest sums for projects of inter-municipal interest, which also seems consistent with the AMT Law.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central government could also test the effectiveness of, and build the capacity of, the AMTs by endowing them with some grant-making capabilities. For example, Rayle and Zegras (2012), in an analysis of inter-municipal collaboration in Portugal, find evidence supporting the role of financial incentives in inducing such collaboration. Perhaps the AMTs could be enabled to deploy modest sums for projects of inter-municipal interest, which also seems consistent with the AMT Law.…”
Section: Discussionmentioning
confidence: 99%
“…According The country's model of metropolitan governance remains loosely coordinated constituent municipal activities, with few and fragmented metropolitan administrative powers, subsidiarity to municipal governments (Oliveira, 2009;Rayle and Zegras, 2012), and a lack of public finance autonomy. Table 1 summarizes the acronyms used to refer to the relevant institutions in Portugal.…”
Section: Fiscal Federalism In Portugalmentioning
confidence: 99%
“…An intermediate question that he attempts to answer from prior work is which factors give rise to inter-municipal collaboration. In that study (Rayle and Zegras, 2013), ad hoc inter-municipal collaboration in relation to land use and mobility in Lisbon and Porto, Portugal, was found to be facilitated by positive incentives (e.g., money), flexibility in the institutional system, the presence of an external catalyst, existing networks, and specific organizational characteristics. The authors found that nearly all of these factors must be present for collaboration to occur.…”
Section: Citizen Engagement and Participation Is Important For Metropmentioning
confidence: 99%
“…Metropolitan governance is limited to fragmented administrative powers, largely subsidiary to municipal governments and dependent on the central government for most financial support (Rayle and Zegras, 2013). The nation has been undergoing a relatively slow process of deconcentration and decentralization, conditioned in part by membership in the quasi-federalist EU system.…”
Section: Portugal: Metropolitan Mobility Governance In a Unitary Systemmentioning
confidence: 99%
See 1 more Smart Citation